The Translation Analysis of Bidding Advertisements Advertised in Newspapers - Regy Geriansyah (Passage, 2013)
The present study entitled The Translation Analysis of Bidding Advertisements Advertised in Newspapers was a case study that focused on investigating the translation procedures used in translating special terms of bidding advertisements advertised in Newspapers from English into Indonesian, and finding out the quality of English-Indonesian translation in Bidding Advertisements Advertised in Newspapers. A descriptive method was applied and the data were organized and analyzed as qualitative data using Newmark’s theories and procedures (1988). In this research, the findings indicated that literal translation procedure was the highest procedure applied in translating the special terms (92 of 200 terms). The finding also showed that the quality of English-Indonesia translation in Bidding Advertisements Advertised in Newspapers was generally good viewed from three aspects; accuracy, clarity and naturalness.Keywords: analysis, translation procedures, bidding advertisements and special term.